Consumer Default, Credit Reporting, and Borrowing Constraints - GARMAISE, MARK J.; NATIVIDAD, GABRIEL (Journal of Finance, 2017)
ABSTRACT Why do negative credit events lead to long‐term borrowing constraints? Exploiting banking regulations in Peru and utilizing currency movements, we show that consumers who face a credit rating downgrade due to bad luck experience a three‐year reduction in financing. Consumers respond to the shock by paying down their most troubled loans, but nonetheless end up more likely to exit the credit market. For a set of borrowers who experience severe delinquency, we find that the associated credit reporting downgrade itself accounts for 25% to 65% of their observed decline in borrowing at various horizons over the following several years.